'Taking Charge of Tourism' - Tourism Social Entrepreneurial Processes in Culion Island, Philippines: An Integrative Model - Aquino, R; Schänzel, Heike; Lueck, M (The Tourism CoLab, 2020)
Tourism social entrepreneurship (TSE) is described as an alternative approach to tourism development, characterised by goals of eradicating local social problems, maximising the positive outcomes of tourism, and delivering sustainable societal transformation (Sheldon, Pollock, & Daniele, 2017). Alongside more efficient resource-use and knowledge exchange, and with social entrepreneurs’ visions, TSE is facilitated through tourism social enterprises: tourism businesses aiming to drive positive social change, usually at the host community level (Aquino, Lück, & Schänzel, 2018; Phi, Whitford, & Dredge, 2017). Although TSE is becoming popular in tourism development practice, there is scant empirical evidence of the processes and activities performed by tourism social enterprises in achieving their social goals. Some previous studies have applied a business model framework in exploring the implementing mechanisms of tourism socia enterprises and understanding how these social ventures operate (Franzidis, 2018; von der Weppen & Cochrane, 2012). However, most of the extant literature on this topic has been developed from pre-determined applied management constructs and the knowledge of tourism social entrepreneurs; these studies have not considered the perspectives of host community actors (e.g. residents). This is a significant omission, as it has been argued that the strategies pursued by tourism social enterprises vary according to their host community, since social entrepreneurial practices are dependent on local conditions. To address this gap in the understanding of tourism social entrepreneurial processes, a constructivist research approach was used. A single case study methodology was employed to explore the processes being facilitated by Kawil Tours, a tourism social enterprise on Culion Island in the Philippines. Culion is an island community commonly known as (formerly) the largest leper colony in the country, which has been engaged in tourism through the initiatives of Kawil Tours since 2011. Case study research was chosen for this study because it enables the in-depth exploration of a phenomenon or organisation bounded by its setting (Stake, 1995). The case study comprised qualitative research methods performed with 19 TSE and host community actors, namely residents, government officials and tourism social entrepreneurs. Fifteen semi-structured interviews and one community engagement workshop were conducted to collect qualitative data. These data collection strategies were supplemented by direct observations and archival research in order to develop a contextual understanding of the phenomenon. Using NVivo 12, grounded theory analysis procedures informed by a constructivist research paradigm were applied to analyse the elicited information (Charmaz, 2014). Cycles of line-by-line, incident with incident, and focused coding schemes resulted in an integrative model that illuminates the processes that are being implemented by the tourism social enterprise. The findings of this study illustrate the emergent categories that comprise the model, which are predominantly social enterprise-led. These categories encapsulate processes and sub-processes that are in parallel with the tourism social enterprises’ economic, social and environmental goals for the community. The paper concludes by critically discussing the degree of community involvement and scale of potential impacts that the emergent tourism social entrepreneurial processes foster in the island community. Finally, the findings of this study are relevant for individuals and social organisations aiming at proliferating community-based TSE activities in localities facing similar social challenges and contextual conditions.
Keywords: Community development; Tourism social entrepreneurship; Social enterprise; Social innovation; Grounded theory